GLOBAL MEDIATIZATION OF INDIAN POLITICS: A COMPARATIVE STUDY OF THE POLITICAL NEWS COVERED BY NEWSPORTALS OF INTERNATIONAL REPUTE DURING UPA AND NDA REGIME - Dr. Amit Sharma , Ashutosh Kumar Pandey (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research paper is an attempt to understand the media coverage of Indian political news. The news portal is considered as true global media. Political faces covered by news portals become prominent across the globe. The samples collected from five news portals of international repute. Based on four parameters, content analysis method has been used to meet the findings. The result indicates that Prime Minister, Chief Ministers and the premiers of other countries have become the most important newsmakers but the President of India does not gains the attention of news portal despite holding the highest constitutional post of the repoublic of India.